BOOK REVIEW OF THE GIRL ON THE TRAIN WRITTEN BY PAULA HAWKINS - Mukti, Nurachni Dwi (LANTERN (Journal on English Language, Culture and Literature), 2016)
Novel is very interesting to be reviewed because the tragedy in the novel occasionally happens in reality, and the author has the ability to dramatize the story. A psychological thriller is interesting for the writer because she has never been in that situation so that the writer can feel the punch of adrenaline that makes her excited and scared at the same time. The content of the novel also makes the writer always curious about what will happen next in the story. The Girl on the Train novel is a psychological thriller which is created by Paula Hawkins as the author.